Teaching psychology to student nurses: the use of 'Talking Head' videos - Sherrill Snelgrove; Desiree J. R. Tait; Michael Tait (Association for Learning Technology, 2016)
Psychology is a central part of undergraduate nursing curricula in the UK. However, student nurses report difficulties recognising the relevance and value of psychology. We sought to strengthen first-year student nurses' application of psychology by developing a set of digital stories based around 'Talking Head' video clips where authentic patients relate their experiences of illness and nursing care. The aim of this article is to discuss the technological, organisational and pedagogical challenges, student and staff evaluations and our recommendations for the future of Talking Heads. First-year student nurses were shown a video clip of a patient talking about their illness experiences followed by a group learning situation linking main themes to psychology and nursing. Students and staff valued the authenticity of patient's narrative, found the video clip easy to follow, reported a raised awareness of psychological concepts and improved empathetic understanding of chronic illness. Negative evaluations were related to a sanitised, untypical representation and limited internet access. This small-scale study highlighted how patient narrative may enhance students understanding of illness experience. It chronicles the development and evaluation of a Talking Head in a specific context but which may be useful across disciplines.